Potential of Lactobacillus casei shirota’s strain against the biofilm-forming of Salmonella Spp - Fauziah, Annisa Rizka; Bahar, Meiska; Ayu Wulandari, Aprilla (POLTEKKES KEMENKES YOGYAKARTA, 2019)
Biofilm of Salmonella spp. is formed through the expression of biofilm genes associated with proteins (bapA) regulated by curli synthesis genes (csg) which carry out adhesion, colonization, maturation, and dispersion on the surface of the intestinal epithelium. This study aimed to determine the antibiofilm activity of Lactobacillus casei Shirota’S strain (LcS) as an inhibitor of Salmonella spp. biofilm formation in vitro. This research was a true experimental study using Microtiter Plate 96 wells Biofilm Assay method. The sample used was the suspension of Salmonella spp. The treatment was in the form of adding a LcS suspension with a concentration series of 10-1;10-2; 10-3;10-4; and 10-5. Biofilm measurements were carried out using a microplate reader and obtained quantitative data in the form of Optical Density at a wavelength of 595nm. The results of this study showed that LcS suspension has antibiofilm activity ranging from 10-5 concentrations with a percentage of 36.58% (p<0.05). The results of exometabolism LcS can reduce Salmonella growth. Exopolysaccharide (EPS) and sortase-dependent proteins (SrtA) of LcS form barriers as competitive adhesion in inhibiting pathogenic biofilm formation.